Modelling response patterns of physico-chemical indicators during high-rate composting of green waste for suppression of Pythium ultimum - St Martin, Chaney C G (Environmental technology, 2014)
High-rate composting studies on green waste, i.e. banana leaves (BL) and lawn clippings (LC), were conducted in 0.25-m3 rotary barrel composters to evaluate and model changes in key physico-chemical parameters during composting. Time to compost maturity and antagonistic effects and relationships of composts against Pythium ultimum were also investigated. Higher temperatures were achieved in LC compost (LCC), which did not translate to higher total organic carbon (TOC) loss but resulted in lower carbon to nitrogen ratio (C:N) and a more mature compost. With the exception of electrical conductivity (EC), net decreases were observed in pH, TOC and C:N across compost types. Total Kjeldahl nitrogen (TKN) showed a net increase in LCC and a net decrease in BLC. With the exception of TOC and pH, the results showed that compost type and time had a significant effect on the respective TKN, EC and C:N models. Compost temperature and TOC were best described by the critical exponential and rectangular hyperbola functions, respectively. Whereas TKN, C:N and pH were described using double Fourier functions and EC using Fourier functions. Composts achieved maturity within 19 days and significantly inhibited the growth of P. ultimum. Bacterial population was positively related to growth inhibition (GI) across compost types, whereas total microbial population had a positive relationship with GI in LCC. Evidence suggests that multiple groups of microorganisms contributed to GI through antibiosis and competition for resources. Composts were determined to be suitable for use as components of plant growth substrates based on compost maturity indices